Meningoencefalite supurativa por Corynebacterium pseudotuberculosis em cabra com linfadenite caseosa: relato de caso - Santarosa, Bianca Paola [UNESP] (2014)
Suppurative lesions in the central nervous system of small ruminants may be caused by Corynebacterium pseudotuberculosis. This report describes a case of suppurative meningoencephalitis caused by C. pseudotuberculosis in goats treated in the Large Animal Clinic of FMVZ-UNESP/Botucatu, SP. The animal had anorexia, caseous lymphadenitis (CL), recumbency, opisthotonus, paddling movements and nystagmus. The CSF showed increased protein and lymphocytic pleocytosis. At necropsy there were localized abscess in the midbrain that after the microbiological culture, resulted in the isolation of C. pseudotuberculosis.